Implementasi Pendidikan Humanistik Melalui Pembelajaran Active Learning di Sekolah Dasar - Aldy Ferdiyansyah; Mubarok (Kilau Publishing, 2025)
Active Learning as one of the humanistic learning models has great potential to improve the quality of learning by activating students and optimizing their potential, so that they can achieve satisfactory learning outcomes according to their characteristics. This study uses a descriptive qualitative approach with the aim of describing the application of the Active Learning model as a humanistic learning model at SDN Tulusrejo 2 with 5th grade students as the research sample. Research data were collected through observation, interviews, and documentation which were analyzed using triangulation techniques. The results of the study showed that the level of student activity was clearly depicted through the role of students as active participants in learning which was seen through question and challenge activities, role reversal questions, peer lessons, team quizzes, and kreasi ceria activities. A series of these activities also had a positive impact on understanding the concept of the material and developing skills such as cooperation, communication, and problem solving. Thus, this study can provide an overview of the application of Active Learning that can be applied through various methods and supporting activities. The implementation of Active Learning in elementary schools shows many benefits and positive impacts on student activity during the learning process so that it can create a humanistic learning climate.